Model Konseptual Pesantren Ramadhan Studi Kasus pada SMK Penerbangan SPAN PADANG - Herry Zulman; Syafruddin Nurdin; Muhammad Kosim (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This writing aims to modify the Ramadan training program initiated by Fauzi Bahar, former Mayor of Padang, about 20 years ago. Implementation of Ramadan 1445H at SMK SPAN Flight Padang was carried out in the same way as the previous year, took place in the campus hall in Jalan By Pass KM.10 Padang. The teaching material is prepared by the Provincial Government Team, and the main activities are carried out by the local religious teachers, with the assistance of several guiding teachers in turn. The method of writing used is library study. Out of a population of 50 people, a random sample of 10 people was taken. The data collected is expected to reveal the benefits and disadvantages of its implementation. Through observations, the author obtains data and information, which is then continued with interviews. Data and information are summarized and simplified before being analyzed and associated with literature. In conclusion, the implementation of the activities is the same as last year, without changing the system and methods, so it does not benefit the character of the participants and misconduct in society. The author proposes a more actual model change: 1. Where the activities are carried out outside the classroom. 2. The instructor is from other Flight Centres. 3. Name of Prophet's friend is used for discussion groups. 4. Use of the Sins Book of the Taruna. 5. System of reward and punishment. 6. Use of information technology during the training activities. 7. Creation of commitments seven advantages of the millennial taruna.